A Primer on Sustainable Business - Open Textbook Library (Open Textbook Library, 2012)
As you read A Primer on Sustainable Business, we challenge you to not think of sustainability as a program, an initiative, or an activity. Rather, sustainability is a mind-set, a philosophy, and worldview. Throughout each chapter, you are challenged to alter the way you view your job, the workplace, the business, and the world. Whether you are an executive, an entrepreneur, or an employee, A Primer on Sustainable Business will help you understand the big picture of what it means to be a sustainable business and will give you the information you need to begin your journey toward sustainability.
Chapter 1: Introduction -- Chapter 2: Operations Management -- Chapter 3: Human Resources -- Chapter 4: Finance -- Chapter 5: Research and Development -- Chapter 6: Marketing -- Chapter 7: IT and MIS -- Chapter 8: Accounting -- Chapter 9: Next Steps: Sustainability Strategy -- Chapter 10: Sustainable Business: Case Examples -- Chapter 11: Appendix: Resources for the Sustainable Business -- References
In English.
Description based on online resource
Keywords: Business -- Textbooks; Finance -- Textbooks; Management -- Textbooks